Skem

trời ơi cứu tui cứu tui

Hoàng Anh Thắng
15 tháng 3 2022 lúc 18:27

Ta có \(\dfrac{a^3}{a^2+b^2}=a-\dfrac{ab^2}{a^2+b^2}\ge a-\dfrac{ab^2}{2ab}=a-\dfrac{b}{2}=\dfrac{2a-b}{2}\)(áp dụng cosi cho \(a^2+b^2\ge2ab\))

\(\dfrac{b^3}{b^2+1}=b-\dfrac{b}{b^2+1}\ge b-\dfrac{b}{2b}=b-\dfrac{1}{2}=\dfrac{2b-1}{2}\)(áp dụng cosi cho\(b^2+1\ge2b\))

\(\dfrac{1}{a^2+1}=1-\dfrac{a^2}{a^2+1}\ge1-\dfrac{a^2}{2a}=1-\dfrac{a}{2}=\dfrac{2-a}{2}\)( áp dụng cosi cho \(a^2+1\ge2a\))

Cộng vế theo vế 

\(\dfrac{a^3}{a^2+b^2}+\dfrac{b^3}{b^2+1}+\dfrac{1}{a^2+1}\ge\dfrac{2a-b+2b-1+2-a}{2}\)\(\ge\dfrac{a+b+1}{2}\left(đpcm\right)\)

Dấu "=" xảy ra <=> a=b=1

Bình luận (0)
Huong Nguyen
15 tháng 3 2022 lúc 17:06

undefined

Bình luận (0)

Các câu hỏi tương tự
Kim Anh Nguyễn
Xem chi tiết
✿.。.:* ☆:**:.Lê Thùy Lin...
Xem chi tiết
✿.。.:* ☆:**:.Lê Thùy Lin...
Xem chi tiết
Trần Thuỳ Linh
Xem chi tiết
Pháttài
Xem chi tiết
Qtrang
Xem chi tiết
Nguyễn Ngọc Thảo
Xem chi tiết
Lê Đặng Mai Anh
Xem chi tiết
Huỳnh Nguyễn Tuấn Nam
Xem chi tiết